2019
DOI: 10.1590/0001-3765201920180140
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive micro-constituents of ackee arilli (Blighia sapida K.D. Koenig)

Abstract: Ackee (Blighia sapida K. D. Koenig) is an exotic fruit widely consumed in the Caribbean countries. While there is extensive research on the presence of hypoglycin A, other bioactive compounds have not been studied. We identified and quantified the changes in bioactive molecules (total phenol, ascorbic acid, hypoglycin A, squalene, D: A-Friedooleanan-7-ol, (7.alpha.), and oleic acid), antioxidant potential, and volatile compounds during two stages of ripe. A clear reduction in hypoglycin A, ascorbic acid, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Also, leaching into the boiling water and the very high temperature of frying, compared to the others, could have resulted in the higher losses observed in these two processing methods. The level of ascorbate measured in the unprocessed aril is lower than the range of 60-66 mg/100 g observed in other studies [19,20]. Similar reductions in ascorbate levels has been reported in other studies upon processing [4].…”
Section: Effect Of Processing On Ascorbate Carotenoids and Phenolic supporting
confidence: 81%
“…Also, leaching into the boiling water and the very high temperature of frying, compared to the others, could have resulted in the higher losses observed in these two processing methods. The level of ascorbate measured in the unprocessed aril is lower than the range of 60-66 mg/100 g observed in other studies [19,20]. Similar reductions in ascorbate levels has been reported in other studies upon processing [4].…”
Section: Effect Of Processing On Ascorbate Carotenoids and Phenolic supporting
confidence: 81%
“…Total phenolic content (TPC) was determined by the Folin-Ciocalteu method as described by Singleton and Rossi [ 32 , 33 ]. The results were expressed as the standard mg gallic acid equivalents (GAE) g −1 of sample dry weight.…”
Section: Methodsmentioning
confidence: 99%
“… ABTS radical cation (ABTS •+ ) scavenging activity assay. The ABTS •+ scavenging activity assay on the methanolic extract of CS and CPHF was determined as described by Grande-Tovar et al., and Re et al., [ 33 , 38 ]. Absorbance values were measured on a spectrophotometer at 734 nm.…”
Section: Methodsmentioning
confidence: 99%
“…This is in agreement with the report of Odutuga et al (1992) who had earlier shown that palmitic acid was the major fatty acid in B. sapida aril from Jamaica. However, other studies have shown that the major fatty acid in B. sapida aril is oleic acid (Tsado et al, 2018;Grande-Tovar et al, 2019). The differences in geographic location as well as processing methods could account for the different results.…”
Section: Discussionmentioning
confidence: 93%